(untitled) (European Journal of Behavioral Sciences, 2024)
Mindfulness meditation-based interventions (MMBIs) are progressively being integrated into the correctional space. The current study investigated behavioral-specific MMBI trends amongst incarcerated populations, focusing on substance use and recidivism. A meta-analytic review of quantitative research explored whether prison MMBIs significantly influence criminogenic behavior. The seventeen studies included in the meta-analytic review were explicitly selected for substance use and recidivism outcomes in prison MMBI research over the past 50 years. Statistical trends in MMBIs were identified and interpreted. Substance use data demonstrated a standardized mean difference of -0.94 with a 95% confidence interval [-1.98 to -0.09]. Recidivism data showed an odds ratio of 1.34 with a 95% confidence interval [1.17 to 1.49]. The pooled effect sizes from both variables were meaningful, demonstrating both tests of overall effect as statistically significant in reducing substance use (p <0.05) and recidivism (p <0.01). The evidence from this research suggested that MMBIs within prisons serve as a valuable program to be incorporated alongside rehabilitation protocols.